An unusual case of uninterrupted inferior vena cava with accessory hemizygous channel: An incidental finding in a child - Gaurav Agrawal (Annals of Cardiac Anaesthesia, 2020)
Azygos or hemizygous continuation of inferior vena cava (IVC) is diagnosed in the presence of intrahepatic interruption of IVC. We report a case of a 4-year-old, male child presenting with a history of poor weight gain. A detailed evaluation of the child revealed a diagnosis of hemizygous continuation of uninterrupted, but severely obstructed, IVC. This incidental finding has rarely been reported in the literature.